2012
DOI: 10.22146/ijc.21368
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Adsorption Properties of Novel Calix[6]arene Polymers for Heavy Metal Cations

Abstract: A research has been conducted to investigate the capability of a series of novel calix [6]arenes-based polymers: poly-monoallyloxycalix [6]arene (2a), poly-monoallyloxypenta-estercalix[6]arene (2b) and poly-monoallyloxypentaacidcalix [6] ABSTRAK Telah dilakukan penelitian untuk mengkaji kemampuan adsorpsi senyawa turunan polikaliks[6]arena yaitu polimonoalilkaliks[6]arena (2a), poli-monoalilesterkaliks[6]arena (2b) dan poli-monoalilasamkaliks[6]arena (2c) terhadap kation logam berat seperti Cd(II), Cu(II) dan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
0
7
0
6
Order By: Relevance
“…The results of the investigation explained that the value of adsorption capacity was Calix [4]resorcinaren > Chitosan > Calix [4] resorcinarene-chitosan (hybrid) [3]. Prabawati, reported that it can be synthesized compounds of p-t.butyl-37-monoallyloxy-38,39,40,41,42-pentahidroxycalix [6]arene and p-t.butyl-575 37,40-diallyloxy-38,39,41,42-tetrahidroxycalix [6]arene then each of them was treated by polymerization reaction in order so can be obtained poly-monoallyloxycalix [6]arene compound [PMK(6)H]arene and polydiallyloxycalix [6]arene compound [PDK(6)H]arene and was applied to study the adsorption kinetics for Cu(II), Cd(II), and Cr(III) [4,5,6]. Calixarene can form complexes with the type of aromatic compounds in a polar solvent non water.…”
Section: Introduction:-mentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the investigation explained that the value of adsorption capacity was Calix [4]resorcinaren > Chitosan > Calix [4] resorcinarene-chitosan (hybrid) [3]. Prabawati, reported that it can be synthesized compounds of p-t.butyl-37-monoallyloxy-38,39,40,41,42-pentahidroxycalix [6]arene and p-t.butyl-575 37,40-diallyloxy-38,39,41,42-tetrahidroxycalix [6]arene then each of them was treated by polymerization reaction in order so can be obtained poly-monoallyloxycalix [6]arene compound [PMK(6)H]arene and polydiallyloxycalix [6]arene compound [PDK(6)H]arene and was applied to study the adsorption kinetics for Cu(II), Cd(II), and Cr(III) [4,5,6]. Calixarene can form complexes with the type of aromatic compounds in a polar solvent non water.…”
Section: Introduction:-mentioning
confidence: 99%
“…Poly-Calix [4]arene-Crown-6 [8,9,10,11], benzyloxycalix [4]arene [12], Calix [4]Resorcine [13,14], calixarene derivative [15], Calix [8] arene Derivative. [16], Bisazocalix [4]arene [17], t-butylcalix [4]arene derivatives [5]. Many attempts have been made to reduce the concentration of heavy metal cations, and guided by a number of facts about the consequences caused by the presence of heavy metal cations, the effort was made to reduce the concentration, especially in the waters.…”
Section: Introduction:-mentioning
confidence: 99%
See 1 more Smart Citation
“…It can be assumed that the availability of hydroxyl group (-OH) and channel-like structure of the polymers can be used as adsorbents for heavy metals. 38,39 Zhu et al produced a calixarene-based microcapsule 33 using a non-agitation solution polymerization. This microcapsule showed the remarkable removing ability for metal cations (Scheme 10).…”
Section: Removal Of Azo Dyes Metal Ions and Toxic Pollutantsmentioning
confidence: 99%
“…Calixarene macrocyclic can be synthesized from aromatic compounds-basic material, both either phenol derivatives and resorcinol. Modifications can be made at the type and number of aromatic units, aldehyde types both aliphatic and aromatic aldehydes [1] or functional group modification with almost unlimited variation [8].…”
Section: Introductionmentioning
confidence: 99%